Challenges and barriers to physician decision-making for prescribing and deprescribing among patients with multimorbidity in eastern China’s primary care settings: a qualitative study - Ming Yan; Zhijie Xu; Andrew Farmer; Yu Xia; Mi Yao; Lingyan Wu; Xinmei Zhou; Liyan Han (BMJ Open)
Objectives Patients with multimorbidity have an increased risk of medication-related problems. Physicians face the dilemmas of multimorbidity management with multiple medications in primary care settings. We aimed to investigate the experiences and perceptions of primary care physicians (PCPs) regarding their decision-making processes in prescribing and deprescribing medications for patients with multimorbidity, and identify the challenges and barriers they face.Design From 5 October 2023 to 27 January 2024, this qualitative study was conducted through semi-structured interviews that encouraged in-depth exploration of the participants’ experiences and perspectives. The interviews were audio-recorded, transcribed verbatim, and independently coded by two investigators. Themes were developed using a conventional content analysis approach.Setting 12 community health centers and 8 township health centers across four regions in eastern China were included.Participants 26 PCPs from 20 primary care institutions in eastern China were interviewed through purposive sampling, representing a mix of urban and rural healthcare settings.Results Of the 26 participants in this study, 14 (53.8%) were women, and the mean age was 36.3 years old. When prescribing and stopping medications for patients with multimorbidity, they often encounter complex challenges. These challenges stemmed from three key areas: (1) difficulties in identifying drug-disease and drug-drug interactions; (2) cognitive biases in medication benefit-risk evaluation and (3) heavy treatment burden. The challenges were further compounded by multiple barriers, including clinical inertia among physicians, patient resistance to medication changes, inadequate decision support and training, and time constraints in clinical consultation.Conclusions The complexity of prescribing and deprescribing decisions faced by PCPs in treating patients with multimorbidity in China is influenced by interconnected factors related to physicians, patients, technology and working environment. Future research could develop and evaluate implementation strategies to address specific challenges and barriers to allow PCPs to make effective medication decisions for patients with multimorbidity.